Assessing the feasibility of simulating different tube current limits in noise oriented ATCM systems. (September 2016) - Mendes, B.; Dias, F.; Oliveira, D.; Sarmento, S.
Abstract : Introduction: Automatic tube current modulation (ATCM) allows automatic dose tailoring in Computed Tomography (CT), according to patient size and anatomical region. In noise-oriented ATCM systems, it is advisable to set minimum and maximum values of tube current (Imin and Imax). Large-scale databases are changing the way medical physicists compare data. Therefore, it is important to understand how an incorrect value of Imin or Imax may be detected from large scale dose distributions. Purpose: To characterize noise oriented ATCM systems from two different vendors, and assess the feasibility of simulating different values of Imin and Imax, for a patient population examined with optimized settings. Materials and methods: A RS-330 Lung/Chest Phantom (RSD, USA) was imaged with different acquisition settings, using scanners GE Lightspeed and Toshiba Aquilion RXL. The tube current as a function of couch position, I(z), was extracted from DICOM headers. For each Imin and Imax, I(z) was compared with the full range curve thresholded to the desired values. Results: The I(z) curves obtained suggest a series of equally-spaced modulation points. Between successive modulation points, I(z) varies almost linearly. The settings of Imin and Imax change the values of I attained at each modulation point, and therefore simulated and real I(z) curves are slightly different. This difference decreases when modulation points are closer together (finer sampling). The sampling depends on equipment and collimation settings. Conclusion: With detailed sampling, differences between simulated and real I(z) curves are below 5%. This difference increases when sampling is less detailed, particularly for lower Imax. Disclosure: The authors have no relevant financial or non-financial relationships to disclose.